Commercial cattle producers: bull selection criteria - Simms, D.D.; Geske, J.M.; Bolze, R.P. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A survey of 312 commercial cattle producers was conducted to determine the relative importance of selection criteria used in buying bulls. Calving ease was a major consideration of a high percentage of producers, and individual performance was being emphasized more than expected progeny differences (EPDs). Only 23% of the producers included EPDs in their first three selection criteria. Visual appraisal focused on structural soundness, length, and muscling.
Keywords: Beef; Bulls; Selection; Breeding; Expected progeny differences